Techniques of geosemiotic analysis (on the basis of Mykolayiv linguistic landscape description) - Chernytskiy, V. B.; Черницький, В. Б. (My University, 2011)
The work deals with urgent methodological issues of urban geosemiotic manifestation analysis from the applied linguistics viewpoint and possibilities of linguistic landscape study on the basis of the technique considered
Методика геосеміотичного аналізу (на основі описання лінгвістичного пейзажу м. Миколаєва)
Chernytskiy, V. B. Techniques of geosemiotic analysis (on the basis of Mykolayiv linguistic landscape description) = Методика геосеміотичного аналізу (на основі описання лінгвістичного пейзажу м. Миколаєва)/ V. B. Chernytskiy // Гуманіт. вісн. НУК. – Миколаїв : НУК, 2011. – Вип. 4. – С. 56–59.
Keywords: geosemiotics; connotation; indexing and symbolizing functions; sovietisms; globalization; геосеміотика; конотація; вказуюча та символізуюча функції; радянськість; глобалізація